A comparison of the effect of Vitamin D and Vitamin E supplementations, alone, and in combination, on reducing the intensity and duration of dysmenorrhea in women: A randomized controlled trial - Tahereh Behrouzi Lak; Nader Aghakhani; Davoud Vahabzadeh; Samereh Eghtedar; Rozita Cheraghi; Nazafarin Ghasemzadeh; Vahid Alinejad; Maryam Mesgarzadeh (Wolters Kluwer Medknow Publications, 2023)
Objective: The aim of this study is to compare the effect of Vitamin D and Vitamin E supplementations, alone, and in combination, on reducing the intensity and duration of dysmenorrhea in women who were referred to the Kowsar gynecological clinics of Shahid Motahari Hospital of Urmia University of Medical Sciences. Materials and Methods: A double-blinded clinical trial was conducted on 112 women with dysmenorrhea who were randomly allocated into the four study groups. Finally, 100 women complete the study and received capsules containing a placebo (n = 25), 1000 IU of Vitamin D (n = 25), 400 mg of Vitamin E (n = 25), and 1000 IU of Vitamin D + 400 mg of Vitamin E (n = 25) every 24 h for 2 consecutive months at the beginning of the menstrual period. The pain intensity and duration among groups were compared before and after the intervention. Results: The mean menstrual pain duration in all three experimental groups (Vitamin E, Vitamin D, and the combination of them) was lower than the placebo group (all P < 0.05), and the mean pain intensity scores in all three experimental groups were significantly lower than the placebo group (all P < 0.05). The results (means) for all of the drugs administered at the end of the 2nd month were better than the 1st month (all P < 0.01). Conclusions: Vitamin E and Vitamin D, as well as their combination, are recommended as an effective and safe treatment for the management of the complications of dysmenorrhea.